Achilles Tendon–Bone Block Allograft for Massive Rotator Cuff Tears With Bony Deficiency of the Greater Tuberosity: A Minimum 2-Year Follow-up Study. Issue 2 (14th February 2022) - Ho, Sean W.L.; Denard, Patrick J.; Chong, Xue Ling; Collin, Philippe; Wang, Sidi; Lädermann, Alexandre
Background: Massive rotator cuff tears associated with greater tuberosity bone loss are challenging to treat. Repairing the rotator cuff without addressing the greater tuberosity deficiency may result in poorer clinical outcomes. Hypothesis: Utilizing an Achilles tendon–bone block allograft to address both the massive rotator cuff tear and greater tuberosity bone loss concurrently can result in improved clinical outcomes. Study Design: Case series; Level of evidence, 4. Methods: The authors performed a retrospective study of patients treated between January 2011 and December 2018 with Achilles tendon–bone block allograft for massive rotator cuff tears associated with greater tuberosity bone loss. The inclusion criteria were massive rotator cuff tear and bony deficiency of the greater tuberosity; patients with a history of bony metabolism disease, connective tissue disease, and previous surgery to the wrist or elbow of the affected limb were excluded. Range of motion, visual analog scale for pain, Constant score, and Single Numeric Assessment Evaluation score were assessed preoperatively and at a minimum of 2 years postoperatively. Radiographs and ultrasound images were evaluated to assess allograft union and rotator cuff integrity. Results: Five patients (3 male and 2 female; mean age, 54.0 ± 12.2 years) were included in the study. The mean follow-up was 80.6 ± 33.7 months. Preoperative to postoperative values improved significantly on the visual analog scale (from 45.8 ± 25.5 to 14.5 ± 14.1; P = .04), Constant score (from 36.8 ± 7.9 to 73.5 ± 3.1; P < .001), and Single Numeric Assessment Evaluation score (from 42.5 ± 26.3 to 82.5 ± 10.4; P = .04). Forward flexion improved significantly from 53° ± 47° to 149° ± 17° ( P = .03). Four of the 5 patients achieved bony union. One patient required removal of symptomatic hardware at 6 months postoperatively, and 1 patient required revision surgery at 1 year postoperatively because of progressive osteonecrosis of the humeral head. Conclusion: In patients with massive rotator cuff tears and a greater tuberosity bony deficiency, utilizing an Achilles tendon–bone block allograft to restore the bony defect and reinforce the rotator cuff repair was safe and effective. At a minimum of 2 years postoperatively, most patients demonstrated improved clinical outcomes, tendon healing, and graft incorporation.